2019
DOI: 10.1016/j.jsurg.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Trauma Surgery Technical Skills Training Courses

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…This is a speculation and requires further investigation. In Mackenzie's review of trauma skills courses in 2018 one major conclusion was that, while all the trauma training improved subjective measures of trauma resuscitation performance, there were very few objective measures studied or available 30 . A recent review of the literature found similar improvements in trauma team performance but few linked to better outcomes 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This is a speculation and requires further investigation. In Mackenzie's review of trauma skills courses in 2018 one major conclusion was that, while all the trauma training improved subjective measures of trauma resuscitation performance, there were very few objective measures studied or available 30 . A recent review of the literature found similar improvements in trauma team performance but few linked to better outcomes 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in evaluation of trauma courses is not unique to LMICs. A review by Mackenzie et al [14] identified 21 trauma skills courses, the majority delivered in high-income countries, and concluded that these programmes are variable in their design, content, duration, cost and resource requirements. In addition, the lack of universal performance metrics and outcomes makes determining the success of these courses difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, further research in the form of prospective controlled trials is required to better answer our research question. Currently, there are limited published studies reporting patient outcomes following simulated trauma training courses [14]. A trial by Bellanova et al [42] identified that individual surgeon and team training was associated with reduced mortality; however, multiple confounding variables greatly limits the strength of this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding this, simulators for emergency open skill procedures are poorly represented in surgical skills curricula. For trauma procedures either part-task trainers of limb structures, (such as a bone or a tendon) or human tissue or animal labs are necessary for simulation in this area [ 17 , 18 ]. Management of extremity injuries often involves a multidisciplinary team such as plastic surgeons, orthopaedic surgeons and vascular surgeons.…”
Section: Introductionmentioning
confidence: 99%